(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
Comic books are experiencing a steady rise in popularity. Not only are they being investigated as subjects of literary studies and other fields of research (e.g., McCloud, 1993; Wolk, 2007; Darius, 2012), they are also getting recognised as instructional resources to improve literacy skills and maintain motivation (O’English, Matthews, Lindsay, 2006). They also have several advantageous features that support foreign language learning. The present study aimed at investigating some of these (guessing meaning of new words; lowered anxiety; better recall) by the use of comic books in the classroom. Three groups of students were recruited (n=14; 14; 8) in a secondary grammar school, as part of the author’s 11-week-long formal English teaching practice.